2015
DOI: 10.1371/journal.ppat.1005066
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic Reactivation of Latent HIV Expression by Ingenol-3-Angelate, PEP005, Targeted NF-kB Signaling in Combination with JQ1 Induced p-TEFb Activation

Abstract: Although anti-retroviral therapy (ART) is highly effective in suppressing HIV replication, it fails to eradicate the virus from HIV-infected individuals. Stable latent HIV reservoirs are rapidly established early after HIV infection. Therefore, effective strategies for eradication of the HIV reservoirs are urgently needed. We report that ingenol-3-angelate (PEP005), the only active component in a previously FDA approved drug (PICATO) for the topical treatment of precancerous actinic keratosis, can effectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
226
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 175 publications
(240 citation statements)
references
References 63 publications
12
226
2
Order By: Relevance
“…It is not known whether this enhancement will occur with the non-globally activating LRAs currently being examined in clinical trials. Many studies are now assessing potential synergistic combinations of different LRAs to achieve more robust latency reactivation, of which some have shown promising results (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…It is not known whether this enhancement will occur with the non-globally activating LRAs currently being examined in clinical trials. Many studies are now assessing potential synergistic combinations of different LRAs to achieve more robust latency reactivation, of which some have shown promising results (44,45).…”
Section: Discussionmentioning
confidence: 99%
“…1, E and F (15). This could be attributed partially to global T cell activation and the absence of cytotoxic T lymphocyte (CTL) response (16,17).…”
Section: Pis Reactivate Latent Hiv In Both Latency Cell Models and Prmentioning
confidence: 99%
“…The latencyreversing agents mainly include histone deacetylase inhibitors, methylation inhibitors, and cytokine (e.g., interleukin-7). Recently, it was reported that ingenol-3-angelate (PEP005), a FDA-approved anticancer drug, can effectively reactivate latent HIV in vitro and ex vivo with relatively low cellular toxicity (Jiang et al 2015). These compounds are potential candidates for advancing HIV eradication.…”
Section: Current Potential Hiv Cure Strategiesmentioning
confidence: 99%